A new freshwater goby of Rhinogobius (Teleostei: Gobiidae) from the Chongkang River basin, Western Taiwan - Chen, I-Shiung (Zootaxa, 2025)
A new freshwater goby of Rhinogobius was recently collected from the Chongkang River basin of Western Taiwan. The new species, Rhinogobius chongkangensis sp. nov., can be well distinguished from all other congeners by the unique combination of the following features: (1) fins: second dorsal fin rays I/9; anal fin rays I/8; pectoral fin rays modally 16; (2) squamation: longitudinal scale series 32–33 (modally 32); perdorsal scales 12–15 (modally 14); (3) vertebral count 27; (4) mouth oblique, rear edge extending to vertical between anterior margin of orbit and anterior edge of pupil in male and (5) specific colouration: lateral body with 7–8 longitudinal rows of small orange to brownish red spots about 1/6–1/10 size of pupil diameter in male; cheek and opercle with 24–32 rather small orange or brownish red spots in male, with 13–16 small brown spots in female; branchiostegal membrane with many 14–18 tiny orange or brownish red spots in male; basal region of first dorsal fin with 8–12 orange or brownish red spots in male, second dorsal fin pale with 3–4 longitudinal rows of orange spots; pectoral fin with two rows of orange to red orange spots which 4–5 larger orange spots or sometimes fusing a vertical line on upper side on anterior row in male; a snow white vertical band between the two rows of orange spots in male. A brief discussion with all nominal congeneric species is also provided.